Acceptance of Implementation of Drug Management and Its’ Barriers on Hospital Management Information Systems - Mygel, Mygel; Septianingsih, Agusdini B; Anindita, Rina (Alta Dharma Publisher, 2024)
Background: The acceptance of management information systems, particularly in the context of drug management. Objective: The study aimed to explore acceptance of the implementation of drug management and its’ barriers on hospital management information systems in pharmaceutical facilities. Method: A qualitative study with a phenomenology approach was applied in this study. eight key informants in this study, consisting of one hospital director, four pharmaceutical officers, two hospital IT officers and one SIMRS vendor. A purposive sampling technique was used to recruited the informant. Result: The results of the study were described understanding of SIMRS such as 1) SIMRS application availability and ease of operation such as description of operating stages, 2) the utility of SIMRS in data calculation and reporting. Challenges of SIMRS application implementation on drug management include 1) unclear job description among pharmacy employee, 2) Restrictions on the return menu of the unit to the other unit on the distribution, 3) error on SIMRS application, and 4) the ability and interest of employees in managing SIMRS. Conclusion: the acceptance of implementation of drug management as a critical to solve the barriers of SIMRS implementation. Recommendation: Hospitals should focus on barriers and acceptance among nurses in order to implement the optimal SIMRS in drug management. Further study needs to develop the intervention to solve the barriers of SIMRS implementation in order to improve the quality of services